2000
DOI: 10.1046/j.1365-2753.2000.00224.x
|View full text |Cite
|
Sign up to set email alerts
|

In the eye of the beholder: problems of perception in designing a strategy to promote evidence‐based clinical policy

Abstract: Independent qualitative evaluation of a project designed to ensure that clinical policy in specific areas of care in three obstetric units within one English health district was based on authoritative evidence. Data from nonparticipant observation, interviews, questionnaires and documents were combined to generate a description of what the project involved and analyses from the perspectives of two key groups of stakeholders: the project proponents and the unit staff whose policies the project was intended to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Models of research use also need to reflect the importance of a common framework in understanding uncertain situations from both a research and a practice perspective. Problem definition is crucial (Humphrey & Berrow 2000).…”
Section: Problem Framingmentioning
confidence: 99%
“…Models of research use also need to reflect the importance of a common framework in understanding uncertain situations from both a research and a practice perspective. Problem definition is crucial (Humphrey & Berrow 2000).…”
Section: Problem Framingmentioning
confidence: 99%
“…Humphrey & Berrow (2000) identify preconceptions about practitioners as an issue. They observed during an EBM clinical policy implementation project that there was an underlying assumption about practitioners that their failure to comply with evidence was not a matter of considered or rational choice, but could be explained rather in terms of deficits of one kind or another, i.e.…”
Section: Applicability Of Research Evidence To Individual Patientsmentioning
confidence: 99%
“…Humphrey & Berrow (2000, p. 171) also recorded that there was an issue with the lack of congruence between topics that were the subject of medical research and those that were of interest to practitioners and patients. They observed that scientific knowledge and local concern were ‘generated for very different reasons’.…”
Section: Applicability Of Research Evidence To Individual Patientsmentioning
confidence: 99%
“…Barriers to implementing evidence-based treatments have been addressed in other domains of medicine [44][45][46]. Emphasis must also be placed on the use of an evaluative process to assess the results of implementation efforts [49]. They also emphasize the importance of the information being delivered, how and to whom.…”
Section: Implementing Clinical Practice Guidelinesmentioning
confidence: 99%